Development of Inquiry-Based Environmental Knowledge Modules and Islamic Values - Emda, Amna; Adam, Mukhlisah; Jannah, Misbahul (Journal of Natural Science and Integration, 2023)
This study aims to assess the feasibility of inquiry-based environmental knowledge modules and Islamic values according to expert assessments. This type of research is research and development which refers to the ADDIE model. The research instrument is in the form of validation sheets from 2 media experts, 3 science material experts, and 2 Quran and tafsir material experts with four assessment categories. The data of this research are observation sheets and questionnaires which are analyzed using descriptive analysis.  The results showed that the feasibility of inquiry-based environmental knowledge modules and Islamic values assessed by media experts was in the feasible category (79%), science material substance experts were in the feasible category (80%) and the substance of the Qur’an and interpretation material experts were in the feasible category (74%). Thus, it can be concluded that the inquiry-based environmental knowledge module and Islamic values can be used in the learning process.Keywords: module, environmental knowledge, inquiry, Islamic values